Understanding the double diaphragm forming process: moving towards multi-component forming - Lendinez Torres, Angela (2025)
Composite materials, formed by combining two or more distinct constituents, offer superior mechanical properties compared to traditional materials, making them essential in industries such as automotive, aerospace, and renewable energy. In advanced manufacturing processes, double diaphragm forming enables the transformation of 2D dry fabric blanks into 3D structures. However, this process presents challenges, including defect formation such as wrinkling and bridging, which can compromise the structural integrity of the final component. As sustainability and process efficiency become increasingly critical, optimising forming techniques is essential. This research focusses on non-crimp fabrics due to their superior mechanical properties and structural performance, investigating key factors influencing defect formation and exploring strategies to enhance the efficiency and sustainability of the double diaphragm forming process.